The Rise of Hedge Funds: A Story of Inequality - Fichtner, Jan (Momentum Quarterly, 2013)
The rise of hedge funds from the almost unnoticed beginnings in the late 1940s to the pinnacle of global finance seventy years later is one of the most pivotal developments for the international political economy. It is the central thesis of this paper that the rise of hedge funds can only be explained by the notion of inequality: inequality between nearly unregulated hedge funds and the regulated rest of financial market actors; inequality between offshore financial centers that provide minimal regulation and low taxation to hedge funds, and onshore jurisdiction that do not; inequality between very rich private individuals that invest in hedge funds and the „bottom 99 percent“ that do not. Two countries play a central role for the rise of hedge funds, the US and the UK. Both adhere to the paradigm of „indirect regulation“ of hedge funds, and both tolerated a drastically increased income inequality since the 1980s that fueled the rise of hedge funds. It is only in these two countries that the story of inequality that drives the rise of hedge funds could be ended.
Keywords: hedge funds; inequality; regulation; financial crisis